Determiner Phrase or Genitive Phrase? An examination of possessive structures in Danish and English - Katballe-Kristensen, Peter (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2022)
This paper seeks to analyze the possessive construction in English and Danish through the lens of two competing analytical frameworks. First, the two frameworks – the Genitive Phrase model and the Determiner Phrase model - are presented and strengths and weaknesses are accounted for. Then, the frameworks are applied to standard possessive constructions from Danish and English. Finally, a unique construction from a dialect of Danish is introduced and tested against the two models. This paper finds that the Determiner Phrase model has a more complete explanation for the different examples.